Assessment of systemic inflammation with neutrophil-lymphocyte ratio in lichen planus - Ataş, Hatice; Cemil, Bengü Çevirgen; Kurmuş, Gökçe Işıl; Gönül, Müzeyyen (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction: Lichen planus (LP) is a papulosquamous eruption of the skin and mucous membranes. Although the exact pathogenesis of the disease remains unclear, it is believed that LP represents an inflammatory disorder. Neutrophil-lymphocyte (N/L) ratio is considered a systemic inflammatory marker that correlated with severity of the diseases. Aim : To investigate whether N/L ratio increases in LP and may be an independent severity marker for LP lesions. Material and methods : White blood cell (WBC), neutrophil and lymphocyte counts, N/L ratio, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) were statistically compared between the patient (n = 55) and the control group (n = 48). The relationship of N/L ratio and the body surface area (BSA) was assessed. Results : Erythrocyte sedimentation rate and CRP were statistically higher in patients with LP than in controls (p < 0.0001). Our analysis revealed a significantly higher level of N/L ratio in patients with LP compared with controls, respectively (2.5 ±1.1 (1.2–7.3) vs. 1.4 ±0.4 (0.8–2.7), p < 0.0001). Body surface area (p = 0.001), CRP (p = 0.006), and ESR (p = 0.003) were identified as possible predictors of N/L ratio, but only BSA (p = 0.002) and ESR (p = 0.003)were found as significant independent predictors in a multiple linear regression model. Conclusions : The inflammatory process in LP was supported by our results. N/L ratio may have an impact to show the inflammatory status in patients with LP as an inexpensive, simple and effective predictor. It may be used for the severity and treatment option of LP. But, N/L ratio and LP relationship could be confirmed by other large prospective studies.